Analisis Kadar Glukosa pada Nasi Putih dan Nasi Jagung dengan Menggunakan Metode Spektronik 20 - Novianti, Muli; Tiwow, Vanny M. A.; Mustapa, Kasmudin (Universitas Tadulako, 2017)
Study on the main content of carbohydrates in rice and corn has been done. This study aims to determine the glucose level in a mixture of corn and rice with a certain ratio prior and during storage in a rice cooker. Spectronic 20 was used in this study to measure the absorption wavelength of sample solutions. Samples used in this study were from rice and sweet corn (Zea mays L. Saccharata) in various ratios of 1:0, 0:1, 1:1, 1:2, 2:1, 3:1 and 1:3, and variations in storage of 0, 1, 6, 12, 18, 24, 30, and 36 hours. The results showed that the highest glucose level in corn were of 32.250 ppm within 12 hours storage, and 40.447 ppm in rice for 12 hours storage. The highest level of glucose in mixture of corn and rice for 12 hours storage was 67.546 ppm at a ratio of 1 : 3.